Review: Integrated Scientific Literacy on Natural Science Learning - Ninda Yera Setyo Nainggolan; Woro Sumarni; Wiyanto; Sutikno; Suharto Linuwih (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2021)
This literature review reveals the journal publication on integrated scientific literacy in natural science learning. A systematic review was carried out through a modified and adopted items selected for the systematic review and meta-analysis (PRISMA). The articles with integrated scientific literacy have been detected in a number of journals, such as ERIC, SCIENCE DIRECT, IJSE, SE, JRST, IOP SCIENCE, DOAJ, and Springer, using the keywords of